Coelomycetes of Assam - III - and N. AHMED3, M.S. ALI1, U.N. SAIKIA2 (Indian Phytopathology, 2002)
Ascochyta bauhiniae sp. nov. and Ascochyta murrayae sp. nov. collected on Bauhinia purpurea L. and Murraya koenigii, respectively, from Assam, India, are described and illustrated.